2006
DOI: 10.1002/meet.1450430148
|View full text |Cite
|
Sign up to set email alerts
|

Image semantics in the description and categorization of journalistic photographs

Abstract: This paper reports a study on the description and categorization of images. The aim of the study was to evaluate existing indexing frameworks in the context of reportage photographs and to find out how the use of this particular image genre influences the results. The effect of different tasks on image description and categorization was also studied. Subjects performed keywording and free description tasks and the elicited terms were classified using the most extensive one of the reviewed frameworks. Differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 19 publications
3
25
0
Order By: Relevance
“…In addition, both Flickr users and indexers were focusing on the description of perceptual attributes and visual characteristics of the images more than interpretive and reactive attributes. These findings are in line with previous research that showed naïve image users using more terms that describe perceptual attributes when viewing individual images (e.g., Jörgensen, 1995Jörgensen, , 1998Laine-Hernandez & Westman, 2006) and using more terms that describe interpretive attributes when labeling groups of images (e.g., Rorissa, 2008;Rorissa & Hastings, 2004;Rorissa & Iyer, 2008).…”
Section: Comparison Of Tags and Index Terms Using Enser And Mcgregor'supporting
confidence: 92%
“…In addition, both Flickr users and indexers were focusing on the description of perceptual attributes and visual characteristics of the images more than interpretive and reactive attributes. These findings are in line with previous research that showed naïve image users using more terms that describe perceptual attributes when viewing individual images (e.g., Jörgensen, 1995Jörgensen, , 1998Laine-Hernandez & Westman, 2006) and using more terms that describe interpretive attributes when labeling groups of images (e.g., Rorissa, 2008;Rorissa & Hastings, 2004;Rorissa & Iyer, 2008).…”
Section: Comparison Of Tags and Index Terms Using Enser And Mcgregor'supporting
confidence: 92%
“…Cluster analysis was done with the average-linkage method used also by Rorissa and Hastings (2004). This produced better results for the current data sets than the complete-linkage method used by Laine-Hernandez and Westman (2006), Lohse et al (1990), Teeselink et al (2000, and Vailaya et al (1998).The quality of the solution was evaluated by calculating the cophenetic correlation coefficient which should be close to 1 for a high-quality solution. The coefficient value of the clustering solution was 0.92 for the context group and 0.81 for the no context group.…”
Section: Clustering Resultsmentioning
confidence: 99%
“…Multivariate analysis methods seek to represent the similarity structures in the image set. Methods used in image categorization research include nonmetric multidimensional scaling (MDS; used, for example, by Laine-Hernandez & Westman, 2006, Lohse, Rueter, Biolsi, & Walker, 1990, and Rogowitz et al, 1998 and hierarchical cluster analysis (conducted, for example, by Laine-Hernandez & Westman, 2006, Lohse, Biolsi, Walker, & Rueter, 1994, Vailaya et al, 1998, and Teeselink et al, 2000. MDS seeks to find a lowdimensional coordinate system to represent the objects using a similarity matrix as data.…”
Section: Methodologiesmentioning
confidence: 99%
“…Markkula and Sormunen (2000) conducted a qualitative study about indexing practices of archivists in a newspaper finding that indexing focused on the concrete content of the photograph. Categorization of journalistic images may also be based on higher level interpretive concepts, including affective and abstract themes (Laine-Hernandez & Westman, 2006). No common frameworks exist for the categorization of journalistic imagery.…”
Section: Introductionmentioning
confidence: 99%